(untitled) (Bangladesh Journal of Urology, 2026)
Ureterocele is a cystic dilatation of submucosal distal ureter. It presents a higher incidence in infants and young children but is rare in adults. The urethral prolapse of ureterocele is extremely rare, and its clinical presentation includes valvular mass, haematuria, and urinary tract dysfunction. This complex case of prolapsed ureterocele in a young female with a protruding mass in the urethral orifice. Bangladesh J. Urol. 2025; 28(2): 131-133